ПРОБЛЕМИ РЕФОРМУВАННЯ ФІНАНСОВОГО ЗАБЕЗПЕЧЕННЯ ВИЩОЇ ОСВІТИ В УКРАЇНІ - Константюк, Наталія Іванівна (Науковий журнал «Світ фінансів», 2017)
Константюк Н. І. Проблеми реформування фінансового забезпечення вищої освіти в Україні. Досліджено фінансування вищої освіти країн, котрі визнано найкращими у світі згідно з рейтингом національних систем вищої освіти. Виявлено пряму залежність між ресурсним забезпеченням вищих навчальних закладів країни, її місцем у рейтингу та розмірами ВВП. Обґрунтовано доцільність інвестицій у вищу освіту, відображено рівень прибутковості при здобутті особою університетського ступеня в розрізі окремих країн. Виділено найважливіші проблеми вітчизняної вищої освіти, котрі мають прямий вплив на фінансування університетів, а в результаті й на конкурентоспроможність на- ціональної системи вищої освіти, а також запропоновано можливі шляхи їх вирішення. Константюк Н. И. Проблемы реформирования финансового обеспечения высшего образования в Украине. Исследовано финансовое обеспечение высшего образования стран, признанных лучшими в мире согласно рейтингу национальных систем высшего образования. Выявлена прямая зависимость между ресурсным обеспечением высших учебных заведений страны, ее местом в рейтинге и размерами ВВП. Обоснована целесообразность инвестиций в высшее образование, отражены уровни прибыльности при получении лицом университетской степени в разрезе отдельных стран. Выделены важнейшие проблемы отечественного образования, которые оказывают прямое влияние на финансирование университетов, а в результате и на конкурентоспособность национальной системы высшего образования, а также предложены возможные пути их решения. Konstantjuk N. Problems of reforming of the financial support of higher education in Ukraine. Introduction. Sufficient funding has direct impact on competitiveness and quality of higher education. According to the ranking of national higher education systems the first countries in the ranking of national systems of higher education are those, which are in the first adequately resourced. Purpose is to prove the expediency of funding and investment in higher education, because higher education always brings economic and social benefits for the country and person. Also it is important to highlight the main problems of the national higher education, which have a direct impact on university funding and competitiveness of national higher education system and find possible solutions for national universities funding. Results. This paper was discovered direct relationship between resources of higher education institutions of the country, its place in the ranking of national systems of higher education and size of GDP. Expediency of investment in higher education was proved. The investments in education are justified for both the country and the individual, and the rates of profit are different for different countries. There are possible solutions for improvement of Ukrainian universities funding were suggested. Conclusion. Higher educational institutions of Ukraine feel the lack of financial resources and it results in looking for alternative ways and resources for funding higher education in Ukraine, which can not be provided without financial independence. If the government today is not able to provide financial funding of higher educational institutions, it should make it possible at least to earn money themselves and to make expenditures on their own. The investment in education, investigations and innovations generate the capital, which is based on knowledge, which contributes to the efficiency and rivalry of nations. That is why the government of Ukraine must take into account these facts while forming the government financial policy for its economic growth, to promote the development of education, which results in scientific investigations, innovations and welfare of the state.